Uniformly convergence of the spectral expansions of the Schrodinger operator on a closed domain - Ahmedov, Anvarjon A. (Institute of Physics Publishing, 2013)
In this work uniformly convergent problems of the eigenfunction expansions of the Schrödinger operator −Δ+q(y1, y2) with singular potential from W12(Ω) are investigated. Using the estimation of the spectral function of the Schrödinger operator on closed domain and mean value formula for the eigenfunction the uniformly convergent of the eigenfunction expansions of the functions continuous on the closed domain is proved.